1989
DOI: 10.1128/iai.57.10.3204-3209.1989
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of coaggregation between Fusobacterium nucleatum and Porphyromonas (Bacteroides) gingivalis by lactose and related sugars

Abstract: The coaggregation of Fusobacterium nucleatum PK1594 and Porphyromonas (Bacteroides) gingivalis PK1924 was inhibited equally well by lactose, N-acetyl-D-galactosamine, and D-galactose, which caused 50% inhibition of coaggregation at 2 mM sugar concentration. Other sugars such as D-galactosamine, D-fucose (6-deoxy-D-galactose), and a-methyland P-methyl-D-galactosides also inhibited coaggregation. Sugar specificity was apparent, since neither L-fucose, L-rhamnose, N-acetyl-D-glucosamine, nor N-acetylneuraminic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
96
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(104 citation statements)
references
References 37 publications
8
96
0
Order By: Relevance
“…Previous studies have shown that coaggregation of oral bacteria is inhibited by specific sugars, often with a structure similar to that of lactose (Kolenbrander & Williams, 1981, 1983McIntire et al, 1982;Kolenbrander & Andersen, 1989;Rickard et al, 2000;Rosen & Sela, 2006). The sugars chosen for this study have previously been used in the characterization of coaggregation between strains derived from the oral cavity (Kolenbrander & Andersen, 1989). The results showed that all of the interactions occurring between oral 13 13 13 13 13 13 13 13 13 13 13 AN/LR 12 12 12 13 12 13 13 13 13 12 and intestinal strains were inhibited to some extent by the addition of individual sugars.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that coaggregation of oral bacteria is inhibited by specific sugars, often with a structure similar to that of lactose (Kolenbrander & Williams, 1981, 1983McIntire et al, 1982;Kolenbrander & Andersen, 1989;Rickard et al, 2000;Rosen & Sela, 2006). The sugars chosen for this study have previously been used in the characterization of coaggregation between strains derived from the oral cavity (Kolenbrander & Andersen, 1989). The results showed that all of the interactions occurring between oral 13 13 13 13 13 13 13 13 13 13 13 AN/LR 12 12 12 13 12 13 13 13 13 12 and intestinal strains were inhibited to some extent by the addition of individual sugars.…”
Section: Discussionmentioning
confidence: 99%
“…Following three washes in phosphate-buffered saline (PBS), the bacterial concentration was spectrophotometrically standardized to OD 650nm = 0.1 for P. gingivalis, corresponding to 10 10 bacteria/mL, 14 and OD 660nm = 0.26 for F. nucleatum, corresponding to 10 9 bacteria/mL. 15 Heat killing was performed at 80°C for 10 minutes. Bacterial viability was determined using blood agar culture.…”
Section: Bacterial Cultivationmentioning
confidence: 99%
“…Coaggregation between P. gingivalis PK 1924 and F. nucleatum PK 1594 is mediated by a galactoside moiety on the P. gingivalis surface and a lectin on the F. nucleatum, and inhibited by lactose, galactose and related monosaccharides (Kolenbrander & Anderson, 1989;Kinder & Holt, 1993;Shaniztki et al, 1997). Polysaccharides (including lipopolysaccharides (LPS) and lipo-oligosaccharides) of various microorganisms were shown to be involved in their adherence to host cells as well as other bacteria (McIntire et al, 1988;Jaques, 1996;Rosen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%